1998
DOI: 10.1097/00001888-199808000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between verbal abuse of medical students and their confidence in their clinical abilities

Abstract: Medical schools must understand that verbal abuse correlates with students' confidence, regardless of their sex, race, age, or levels of ability and assuredness. School policies must address the problem of verbal abuse of students to avoid lowering students' self-confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
0
32
0
3
Order By: Relevance
“…Until now no quantitative data charting UK medical students’ experiences of bullying has been published although valuable qualitative studies have highlighted problematic aspects of students’ socialisation into medicine and revealed the ‘hidden curriculum’,8–10 which Hafferty describes as ‘a set of influences that function at the level of organisational structure and culture’ 11. Elsewhere research has revealed the professionalism dilemmas for students that result from poor role-modelling,12 13 and the negative impact on students’ confidence in clinical skills 14. International research confirms this rather bleak picture 15 16…”
Section: Introductionmentioning
confidence: 99%
“…Until now no quantitative data charting UK medical students’ experiences of bullying has been published although valuable qualitative studies have highlighted problematic aspects of students’ socialisation into medicine and revealed the ‘hidden curriculum’,8–10 which Hafferty describes as ‘a set of influences that function at the level of organisational structure and culture’ 11. Elsewhere research has revealed the professionalism dilemmas for students that result from poor role-modelling,12 13 and the negative impact on students’ confidence in clinical skills 14. International research confirms this rather bleak picture 15 16…”
Section: Introductionmentioning
confidence: 99%
“…It also degrades the way they are portrayed in the literature and media as “scut puppies” who are supposed to follow the whims of the master in order to avoid compromising their career and repute 7. Besides, student abuse and maltreatment result in less effective development of students, both personally and professionally, such that they are less likely to ask for advice or help when needed 9. Verbal abuse causes even the most resilient of students to lose self-confidence 10,11…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, verbal mistreatment affects students’ confidence in their clinical abilities and their ability to succeed in residency. 4,5 …”
mentioning
confidence: 99%